CO2 Absorption in Aqueous Monoethanolamine/Methyldiethanolamine/ Diethylenetriamine and Their Blends Solutions - Yang, Jian; Wen, Juan; Wu, Guofang; Liu, Qingcai; Kirk, D.W.; Bao, Simin (Asian Journal of Chemistry, 2012)
This paper compares the loading and extent of CO2 uptake by various amines and their mixtures. A quantity of CO2 was introduced into a 292 mL stainless steel batch reactor containing 10 mL amine solutions at a constant temperature, then the reactor was sealed, pressurized with a CO2 containing gas and the system pressure was recorded. The CO2 absorption into the amines was recorded as a pressure decrease and used to calculate the amount and loading of CO2 in the amines. In particular, diethylenetriamine was found to be effective in enhancing the performance of other amines. Diethylenetriamine was added into aqueous monoethanolamine and methyldiethanolamine solutions and its effects were investigated. The results indicated that CO2 removal extent and absorption amount increased with aqueous amine solution concentration, while CO2 loading decrease with aqueous amine solution concentration. diethylenetriamine has a good absorption characteristic and adding a small quantity of diethylenetriamine was found to promote the absorption characteristics of monoethanolamine or methyldiethanolamine aqueous solutions.